Linux [ the complete reference - Petersen, Richard , 1949- (McGraw-Hill, 2008)
Explaining each aspect of Linux, this work gives you details on the Linux kernel, Gnome and KDE, window managers, multimedia tools, Web, FTP, and Mail services, file systems, print servers, and backup procedures. It also includes coverage of security protocols, network automatic configuration, IPv6, Yum, Xen, and virtualization technology.